Diagnostic serum vitamin D level is not a reliable prognostic factor for resectable breast cancer. (9th May 2018) - Mizrak Kaya, Dilsa; Ozturk, Bengi; Kubilay, Pinar; Onur, Handan; Utkan, Gungor; Cay Senler, Filiz; Alkan, Ali; Yerlikaya, Halis; Koksoy, Elif B; Karci, Ebru; Demirkazik, Ahmet; Akbulut, Hakan; et al.
Aim: There are inconsistent results about the effects of vitamin D level on breast cancer prognosis. We aimed to investigate the effect of vitamin D levels on the prognosis of resectable breast cancer in a patient group with highly different clothing styles.Patients & methods: A total of 186 breast cancer patients were enrolled in the study.Results: Vitamin D level was sufficient, insufficient and deficient in 17.2, 52.2 and 30.6% of patients, respectively. There was a significant relationship between clothing style and serum 25 (OH) D levels. We could not establish any relation between vitamin D level and tumor characteristics or survival.Conclusion: Vitamin D supplementation can be more important than diagnostic serum vitamin D level on prognosis of breast cancer.